Evaluation of the Effects of Khat Chewing and Cigarette Smoking on Liver and Kidney Functions among Students at Taiz University, Yemen - Salwa Abdul-Ghani Abdul-Rahman Al-Shamiri (Indian Journal of Medical Biochemistry)
Aims and background: Khat chewing and smoking are some of the most popular social activities in Yemen. However, little is known about how these habits affect the liver and kidney, so this study was made to examine the potential effects of these habits on the levels of various biochemical parameters to evaluate kidney and liver functions in healthy medical students that were considered as khat chewers and smokers. Materials and methods: In total, 90 healthy medical students took part in this investigation. The biochemistry of the liver and kidneys was assessed on 30 khat chewers only, 30 khat chewers and smokers, and 30 non-khat chewers and nonsmokers. Results: The activity of the AST, ALT, and GGT enzymes reveals a significant increase among khat chewers and khat chewers and smokers’ groups. A significant correlation was observed between the duration of both khat chewing and cigarette smoking and the levels of creatinine uric acid, albumin, and GGT. Conclusion: We come to the conclusion that Catha edulis with amphetamine-like effect and the cytotoxic effects of cigarette smoking might be responsible for hepatocellular and kidney damage with a correlation to the khat chewing and smoking durations.